Asset and liability management : comparative study of conventional and Islamic banks in Malaysia - Htay, Sheila Nu Nu; shuib, Siti Sufiya (2011)
This study evaluates the asset-liability management of both Islamic banks and Conventional banks in Malaysia, pre and post global financial crisis 2007/2008. The purpose of this study is to verify whether or not there are any significant difference between the Islamic banks in Malaysia than its conventional counterpart in terms of interest (profit) rate risk, credit risk and liquidity risk management, before and after the global crisis as the Islamic banks operate under different framework and fundamental. This study applies descriptive method of research and independent sample t-test.